Pelatihan Produk "Green Economy" untuk mempersiapkan Wirausaha Muda Ramah Lingkungan di Kecamatan Kupang Tengah: “Green Economy” Product Training to Prepare Young Environmentally Friendly Entrepreneurs in Kupang Tengah District - Olivia Louise Eunike Tomasowa; Cicilia Apriliana Tungga; Yemima Eka Christi Windya; Soni Doke (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This Science and Technology Program for the Community (PKM) aims to solve the partner's problem, which is to teach the younger generation in Kupang Tengah District the importance of entrepreneurship and to combine it with the concept of the Green Economy, how the Green Economy concept can be the basis for youth entrepreneurship, thereby increasing their income. The solution offered is to combine the Green Economy concept with entrepreneurship, focusing on creating business opportunities by producing environmentally friendly products. Based on preliminary research, plastic waste, especially bottles, is abundant and a concern for the community because it is considered waste with no added value. We want to provide knowledge about entrepreneurship and the Green Economy concept. We want to combine these two things to create and build new businesses for young people in Kupang Tengah. The product to be produced is a sofa made from bottle waste. Entrepreneurial collaboration on the concept of the green economy will produce products with market value and environmental benefits. The increased ability of partners to produce "Green Economy Products" (Environmentally Friendly) with market value. (2). The formation of new young entrepreneurs (Entrepreneurs), (3). The "Sofa" product, which is a "Green Economy Product" (Environmentally Friendly) with market value. Partner participation in this activity involves preparing participants to join and sourcing the primary raw material: plastic bottle waste.